Crunch point : the 21 secrets to succeeding when it matters most - Tracy, Brian (American Management Association, 2007)
In business and in life, things seldom go exactly as planned. You've probably figured out how to navigate around the little bumps, but what about full-blown crises, the kind with the potential to derail a company or send your personal life spinning out of control? Crunch Point presents a series of proven, practical techniques for overcoming any setback that may come your way -- on the job, at home, or anywhere in your life. In an accessible, no-time-to-lose format, success expert Brian Tracy gives you the motivation, techniques, and confidence to grab tough and urgent problems by the horns and solve them -- quickly, decisively, and completely. Crunch Point reveals Tracy's 21 proven ways to: * Take control of the situation. * Stay calm and rational -- even in a crisis. * Communicate clearly, constantly, and authoritatively with the key people around you -- the skill that can make all the difference between failure and success. * Identify and remove all obstacles to resolving the problem. * Deal with problems more effectively by handling them systematically instead of randomly or emotionally, as most people do. * Develop unshakeable courage and super-high self-confidence. * Generate cash flow when the crisis is financial in nature. * Never lose focus on your customers, no matter how dire the situation may seem * Cut your losses, when necessary, and save time and money in the long run. Each chapter offers a selection of problem-solving strategies, complete with powerful action steps you can take regardless of the nature or size of the problem. It's inevitable: At some point, the you-know-what is sure to hit the fan. Dealing with a crisis may never be easy or pleasant, but with the universal problem-solving techniques presented in Crunch Point, you'll have the confidence and skills to rise above whatever comes your way -- and you'll be the one everyone calls 'great under pressure.'